Evaluation of Nanoparticles Based Gels from Extraction of Different Fruit Peels - Kanwar Madhu; Choudhary Suresh (Current Research in Pharmaceutical Sciences, 2023)
Nanoparticles are particles ranging in size from 1 nm to 100 nm. Triangles, spheres, irregular shapes, etc. They come in different sizes such as. In recent years, the synthesis of nanoparticles has received widespread attention due to their unique properties and potential applications. The powder sample (100gm) was extracted with 800ml ethanol using Soxhlet extraction method for 6 hours. The resulting extract is used in the preparation of nanoparticles. The main objective of the present work was to prepare green apple and orange peel extract based nano particles by chemical complexation method. Ethanol extracts of green apple and orange peel were prepared using Soxhlet extractor and analyzed for their phytochemical composition. qualitative analysis of green apple peel showed positive results for alkaloids, anthraquinones, saponins and terpenoids, while orange peel showed positive. Good results for alkaloids, tannins and saponins. The moisture percentage of two fruits (green apple and orange) is 72% and 96.12% respectively. Green apples and oranges have a pH of 3.6 and 3.8 respectively. The zeta potential of green apple extract nanoparticles is -24.6 mV to -34.5 mV (P20 and P50), and the zeta potential of orange extract is -21.4 mV to 32.0 mV (O20 and O50). For nanoparticles these values are higher, indicating less potential for aggregation. The size of the apple extract varies from 118.6 nm to 231.7 nm (P20 and P30), while the size of the orange extract varies from 178.8 nm to 191.6 nm (O20 and O50). This line confirms that the obtained particles are in the nanometer range, i.e. <500 nm in size. SEM results show the formation of nanoparticles and their shape is spherical. Energy dispersive spectroscopy (EDS) analysis confirmed the presence of silver nanoparticles. Silver nanoparticles were prepared using green and orange juice peels. Computability studies FT-IR showed that there was no change in the functional group of the shell in the prepared nanoparticles. Zeta potential indicates higher efficiency and therefore less particle aggregation. The prepared nanoparticles are spherical in shape and have a particle size of approximately 200 ± 20nm. Further the study will be extended for anti- microbial and wound healing activities.